Magnetic Susceptibility of Pumice at Mount Singgalang, West Sumatera - Miftahul Arrazi; Hamdi Rifai; Fatni Mufit; Harman Amir (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
Volcanic activity produces eruptions that release pyroclastic material at the time of the explosion. Mount Singgalang is a volcano that has experienced an eruption after 1600. Several types of volcanic rocks around the Mount Singgalang area are Basalt, Andesite, Tuff Breccia, Lava Breccia, and Pumice Tuff. Pumice is formed when saturated liquid magma gas bursts like a carbonated beverage and soon cools, causing the froth that results to solidify into a glass full of gas bubbles. Some minerals contained in pumice are obsidian, cristobalite, feldspar, and tridymite. Pumice contains magnetic minerals, namely ilmenite (FeTiO3), and magnetite (Fe3O4). The purpose of this study is to quantify the magnetic susceptibility and quantity of pumice on Mount Singgalang in West Sumatera. When utilizing the Bartington Magnetic Susceptibility Meter to analyze a sample, magnetic susceptibility parameters are utilized to pinpoint the features of a magnetic rock mineral. The value of the magnetic susceptibility of pumice on Mount Singgalang, in West Sumatera has a value that varies between 2763.3 x 10-8m3/kg - 2192.1 x 10-8m3/kg. The results showed that the tested samples had antiferromagnetic magnetic mineral properties with frequency-dependent susceptibility values (χfd), indicating that all of the measured samples contained almost no superparamagnetic (SP) grains and were generally dominated by multi-domain (MD) grains.